Navigating between worlds: An autoethnography of a first-generation international PhD student's first year - Ma, Anyi (Journal of International Students, 2026)
The doctoral stage is often described as an isolating and individualistic journey, making belonging particularly challenging. Sense of belonging is closely linked to doctoral persistence, especially in the early stages, when marginality is heightened. As first-generation and international doctoral populations grow, understanding how belonging develops in the first year becomes increasingly important. This study draws on autoethnography and is informed by Van Gennep’s rites-of-passage framework to explore the first-semester experience of an international, first-generation PhD student. Through iterative reflection and interpretive analysis, the study traces how belonging emerges through moments of uncertainty, interaction, and adjustment. The findings show that belonging is a dynamic, processual experience that is unevenly negotiated across shifting academic, social, and cultural contexts. The study develops a process-oriented mapping of early belonging formation, extending the literature by foregrounding temporality and transition.